USAHA-USAHA MEMASYARAKATKAN HUKUM DI DALAM MASYARAKAT - ARPAN ZAMAN (JCH (Jurnal Cendekia Hukum), 2018)
This research was discussed about the way to socialize law in the society such as law education and how to maintain the law in the right place such as law education, law knowledge, society understanding about law, law structure, law culture and law substance. Besides, this research aims at knowing about the obstruction in socializing. This research was a library research by describing the problems with the relevant theories. The result of this research shows that in socializing the law in the society, it needs a lot of things to be done such as, willingness, education, supports from the environment, custom and culture, and awareness to obey toward the law in the society sincerely without any force. Furthermore, counseling, socialization and seminar are the way to make it easy in socializing the law in the society. Whereas, the obstruction in socializing the law are dominated by the level of education and knowledge had by the society, custom and culture in that place that is grew and developed, law structure, apparatus and law substance.